World Conference on Timber Engineering (WCTE 2023) 2023
DOI: 10.52202/069179-0508
|View full text |Cite
|
Sign up to set email alerts
|

Towards Design Flexibility and Freedom in Multi-Storey Timber Construction: Architectural Applications of a Novel, Adaptive Hollow Slab Building System

Abstract: This paper discusses the architectural design potentials of a novel hollow timber slab building system for flexible and adaptive multi-storey timber building typologies. Current timber building systems are defined by their standardized nature, which limits most structures to unidirectional, rigid grids and limits designs to rectilinear layouts. At the same time, recent developments in computational design and digital fabrication open new possibilities to overcome these limitations. In this paper we present fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although the building prototype incorporated electrical conduits into the slab, much work is required to turn a structural system into an inhabitable building. Svatoš-Ražnjević et al [95] have shown in initial studies how mechanical, ventilation, electrical, and data services could fit inside a hollow slab system. The integration of additional building services, including plumbing, ventilation, and telecommunications, to name a few, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the building prototype incorporated electrical conduits into the slab, much work is required to turn a structural system into an inhabitable building. Svatoš-Ražnjević et al [95] have shown in initial studies how mechanical, ventilation, electrical, and data services could fit inside a hollow slab system. The integration of additional building services, including plumbing, ventilation, and telecommunications, to name a few, requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Discretised webs allow for further service integration in the slab. For example, web arrangements can be adapted to the layout of integrated services [95]. Structural, fabrication, and design considerations were integrated into a single model built on a multi-level, multi-agent simulation in accordance with co-design principles [100].…”
Section: Design Methodsmentioning
confidence: 99%
See 1 more Smart Citation